Asymptomatic deficiency in the peptide transporter associated to antigen processing (TAP) - SALLE, H DE LA (Blackwell Science Inc, 2002)
Human HLA class I deficiency is a rare disease which, in most of the patients described to date, results from a defect in subunit 1 or 2 of the peptide transporter associated with antigen processing (TAP). The clinical features of TAP deficiency include a chronic inflammation of the respiratory tract and/or granulomatous skin lesions. In this report, we describe two adult siblings with an HLA class I deficiency. One individual had only spontaneously-healing skin granulomatous lesions, while the second did not display any of the symptoms associated with HLA class I deficiency and could be considered to be healthy. We show that the patients display a homozygous TAP2 mutation which blocks the maturation of HLA class I molecules. Cell surface expression of these molecules is strongly reduced, but three times higher than on cells from other previously described TAP-deficient individuals. This higher expression results, at least in part, from the presence of HLA-B7 molecules which are probably empty of peptide. The numbers of CD8(+) αβ T cells are almost normal in these patients. The anti-EBV T-cell response of one patient is mediated by HLA-B7 restricted CD8(+) αβ T lymphocytes recognizing the BMRF1 nuclear EBV antigen, demonstrating that CD8(+) αβ T cells can participate in anti-viral responses. This study shows that TAP deficiency can remain totally asymptomatic for several decades, and suggests that in some cases, TAP-independent immune responses provide efficient protection from most of the common intracellular pathogens.